Pendekatan Inklusif Oleh Kepolisian Dalam Memberikan Perlindungan Hukum Bagi Anak Disabilitas Korban Kekerasan Seksual - Ramadhani. D, Anggia Nur; Siswanto, Heni; Irzal Fardiansyah, Ahmad; Rosidah, Nikmah; Fathonah, Rini (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Cases involving people with disabilities who become victims of sexual violence continue to increase from year to year and often do not receive adequate attention, both from a legal and social perspective. In fact, this group needs stronger legal protection because the limitations they have often become obstacles in fighting for justice. The police have a crucial role in providing legal protection based on an inclusive approach for children with disabilities who are victims of sexual violence. This study aims to ensure that the legal protection provided by the Police can be just and equal. The method used is normative legal research with a legislative and conceptual approach, as well as qualitative analysis of primary and secondary legal materials. The results of the study show that the inclusive approach carried out by the Police is interpreted as a method of service and handling that guarantees equality without discriminating between conditions, as well as fulfilling the special needs of children with disabilities without physical, communication, or attitude barriers. The inclusive approach is carried out through the provision of professional assistance, the use of easily understood language or sign language, and the creation of a safe and child-friendly environment